Variability of Australopithecus second maxillary molars from Sterkfontein Member 4. Issue 85 (August 2015) - Fornai, Cinzia; Bookstein, Fred L.; Weber, Gerhard W.
Abstract: The question of how many Australopithecus species lived at Sterkfontein Member 4 and Makapansgat continues to be controversial inasmuch as the fossils are poorly preserved, the stratigraphy is difficult to interpret, and the cranial, dental, and postcranial remains are mostly not associated. To proceed we applied the most intensive modern methods of 3D geometric morphometrics to dental form, specifically the shapes of the upper second molars (M 2 s) in a sample combining 13 Australopithecus, 11 Paranthropus, and 23 Homo . We analyzed outer and inner crown surfaces, as well as crown and cervical outlines both separately and together, using a total of 16 landmarks, 51 curve semilandmarks, and 48 pseudolandmarks over the four structures. Outer and inner enamel surfaces are highly correlated in this dataset, while crown outline is the least informative of the four structures. Homo was easily distinguished from both Australopithecus and Paranthropus by these methods, likewise Homo sapiens from Homo neanderthalensis . There were, however, no stable classes within the Australopithecus sample or between Australopithecus and Paranthropus . Instead, there was a gradient along which Australopithecus prometheus and Australopithecus africanus lie toward the extremes, with Paranthropus overlapping both. If there are indeed different species at this site, then either their M 2 morphologies are uninformative or else the present sample is too small to make an accurate assessment. Our findings suggest that the variability of the Australopithecus specimens will be difficult to interpret authoritatively, independent of the method used.